Goodbye Mao. Szwedzkie powieści kryminalne jako próba rozliczenia pokolenia `68 = Goodbye mao - swedish crime fiction as an attempt to settle with the past of the 68ers - Samsel-Chojnacka, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The generation entering adulthood in the late sixties left a profound mark on the modern history of Sweden. Rebellious and disobedient towards the values of the "third way", which had been set between socialism and capitalism by the Social democratic Party, the young radicals reproached their parents with betraying the social solidarity ideals.
Keywords: literatura szwedzka - tematyka - 21 w.; powieść kryminalna